Biodegradable non-woven fabric and preparation method thereof

By adding biodegradable mother grains in polypropylene non -woven fabrics, modified shell polycosaccharides, and macarin anhydride polypropylene and other raw materials, the problem that traditional non -woven fabrics are difficult to degrade, and the high -broken strength and high degradation rate are achieved. Non -woven fabric.

CN119352227AActive Publication Date: 2025-01-24山东华业无纺布有限公司
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411404035.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-24
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

Traditional polypropylene non-woven fabrics are difficult to degrade, resulting in environmental pollution.

Method used

Polypropylene, biodegradable maternal particles, modified chitosan, and macarin anhydronic polypropylene and other raw materials are used to improve the fracture strength and degradation rate of non -woven fabrics by cooperating with each other.

Benefits of technology

It has achieved high breaking strength and high degradation rate of non-woven fabrics. The longitudinal breaking strength is >74N, the transverse breaking strength is >60N, and the 180-day degradation rate is >90%, which solves the problem that traditional non-woven fabrics are difficult to degrade.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352227A_ABST
    Figure CN119352227A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of non-woven fabrics, and particularly discloses a biodegradable non-woven fabric and a preparation method thereof. The non-woven fabric is mainly prepared from the following raw materials in parts by weight: 100 parts of polypropylene, 1-2 parts of biodegradable master batch, 6-8 parts of modified chitosan, 3-5 parts of maleic anhydride grafted polypropylene and 1-2 parts of antioxidant. The modified chitosan is obtained by treating chitosan with sodium hydroxide, 1-chlorododecane and 4-(2-chloroethane acylamino) ethyl benzoate. The biodegradable non-woven fabric has the advantages of being high in breaking strength and good in degradability, the application range is widened, the problem of environmental pollution caused by the fact that traditional polypropylene non-woven fabric is difficult to degrade can be solved, and market requirements are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of nonwoven fabrics, and more specifically, to a biodegradable nonwoven fabric and a preparation method thereof. Background Art

[0002] As an important material, non-woven fabrics have been widely used in the fields of medical care, industry, agriculture, etc. In recent years, as people pay more and more attention to environmental protection issues, more and more researchers have begun to pay attention to biodegradable materials to reduce the impact on the environment. Traditional non-woven fabrics are made of polypropylene or polyethylene as raw materials. Although they have the advantage of low cost, they are difficult to degrade after long-term use, which brings a heavy burden to the environment. Based on this, the development of a biodegradable non-woven fabric has become a new topic to meet market demand and expand industry applications. Summary of the invention

[0003] In order to improve the degradability of non-woven fabrics, the present application provides a biodegradable non-woven fabric and a preparation method thereof.

[0004] In a first aspect, the present application provides a biodegradable nonwoven fabric, which adopts the following technical solution: A biodegradable nonwoven fabric is mainly made of the following raw materials in parts by weight: 100 parts of polypropylene, 1-2 parts of biodegradable masterbatch, 6-8 parts of modified chitosan, 3-5 parts of maleic anhydride grafted polypropylene, and 1-2 parts of antioxidant; the modified chitosan is obtained by treating chitosan with sodium hydroxide, 1-chlorododecane, and 4-(2-chloroethane acylamino) ethyl benzoate.

[0005] The biodegradable non-woven fabric of the present application, through the mutual cooperation between the raw materials, has a longitudinal breaking strength of >74N, a transverse breaking strength of >60N, and a 180-day degradation rate of >90%, showing the advantages of high breaking strength and good degradability, meeting market demand, and being able to solve the environmental pollution problem caused by the difficulty in degradation of traditional polypropylene non-woven fabrics.

[0006] The non-woven fabric uses polypropylene as the main raw material, and on this basis, maleic anhydride grafted polypropylene is added to the raw material to increase the compatibility between the raw materials. Biodegradable masterbatch and modified chitosan are added to the raw material, and the mutual cooperation between them is utilized to improve the degradation rate and enhance the degradability without affecting the breaking strength of the non-woven fabric, so that the non-woven fabric exhibits better mechanical properties. Further, 1-chlorododecane and 4-(2-chloroethane acylamino) ethyl benzoate are used for chitosan, and active groups such as dodecyl, ester group, and amide group are introduced on the surface of chitosan to increase the compatibility of the modified chitosan and the binding force and integrity between the raw materials. On the basis of not affecting the degradation rate of the non-woven fabric, the breaking strength of the non-woven fabric is significantly increased, so that the non-woven fabric exhibits better mechanical properties.

[0007] Optionally, the modified chitosan is prepared by the following method: S1. Mix water, isopropyl ketone, chitosan, sodium hydroxide and tetramethylammonium hydroxide at a temperature of 40-60°C, and stir for 1-3 hours to obtain chitosan alkaline solution; S2. Add 1-chlorododecane and ethyl 4-(2-chloroethaneylamino)benzoate to the chitosan alkaline solution at a temperature of 60-80°C, keep the temperature for 7-9 hours, cool to room temperature, adjust the pH value to 6.5-7.5, add acetone for precipitation, filter, wash, and dry to obtain modified chitosan.

[0008] Optionally, the weight ratio of chitosan, sodium hydroxide, 1-chlorododecane and ethyl 4-(2-chloroethaneylamino)benzoate is 10:(9-11):(4-6):(4-6).

[0009] By adopting the above technical scheme, chitosan is firstly treated with sodium hydroxide to alkalize the chitosan, so that the -OH on the surface of the chitosan is converted into -ONa, and then the chlorine groups in 1-chlorododecane and 4-(2-chloroethane acylamino) ethyl benzoate are substituted to achieve grafting. The chitosan modification method of the present application is not only convenient for the preparation of modified chitosan, but also limits the addition amount of sodium hydroxide, 1-chlorododecane, and 4-(2-chloroethane acylamino) ethyl benzoate to ensure the grafting amount, and also ensures the stability of the preparation of the modified chitosan and the use effect.

[0010] Optionally, the weight ratio of chitosan, water, isopropyl ketone, tetramethylammonium hydroxide and acetone is 10:(15-25):(70-90):(1-3):(80-120).

[0011] By adopting the above technical solution, the addition amount of water, isopropyl ketone and tetramethylammonium hydroxide is optimized, so that chitosan, sodium hydroxide, 1-chlorododecane and ethyl 4-(2-chloroethane acylamino)benzoate are fully mixed to facilitate the reaction. The addition amount of acetone is also optimized to fully precipitate the modified chitosan and ensure the stability of the preparation of the modified chitosan.

[0012] Optionally, the deacetylation degree of the chitosan is 85-95%.

[0013] By adopting the above technical scheme, the deacetylation degree of chitosan is optimized, which is convenient for the selection of chitosan, and the solubility and physical properties of chitosan are guaranteed, which is convenient for the modification of chitosan. In multiple embodiments, the deacetylation degree of chitosan is 90%, and the deacetylation degree can also be set to 85%, 88%, 83%, 95% as required, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0014] Optionally, the average molecular weight of the chitosan is 50,000-150,000. In multiple embodiments, the average molecular weight of chitosan is 50,000, and the average molecular weight can also be set to 70,000, 100,000, 130,000, or 150,000 as required, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0015] Optionally, in step S2, a hydrochloric acid aqueous solution is used to adjust the pH value to 6.5-7.5, and the mass concentration of the hydrochloric acid aqueous solution is 5-10%.

[0016] By adopting the above technical solution, the pH value is adjusted by using hydrochloric acid aqueous solution, which is simple and convenient. The mass concentration of the hydrochloric acid aqueous solution is also limited, which is convenient for the preparation and use of the hydrochloric acid aqueous solution.

[0017] Optionally, the polypropylene has a melt index of 30-40 g / 10 min at 230° C. and 2.16 kg.

[0018] By adopting the above technical solution, the melt index of polypropylene is limited to ensure the stability of the source of polypropylene and the quality and stability of the non-woven fabric. In multiple embodiments, the melt index of polypropylene at 230°C and 2.16 kg is 35 g / 10 min. The melt index can also be set to 30 g / 10 min, 33 g / 10 min, 38 g / 10 min, and 40 g / 10 min as needed, but it is not limited to the listed values. Other values ​​not listed in the numerical range are also applicable.

[0019] Optionally, the maleic anhydride grafted polypropylene has a melt index of 100-150 g / 10 min at 230° C. and 2.16 kg.

[0020] By adopting the above technical solution, the melt index of maleic anhydride grafted polypropylene is limited to ensure that the raw materials are fully mixed, increase the compatibility of the raw materials, facilitate the processing of non-woven fabrics, and improve the mechanical properties of non-woven fabrics. In multiple embodiments, the melt index of maleic anhydride grafted polypropylene at 230°C and 2.16kg is 120g / 10min, and the melt index can also be set to 100g / 10min, 110g / 10min, 130g / 10min, 140g / 10min, 150g / 10min as needed, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0021] Optionally, the antioxidant is one or more of antioxidant 1010, antioxidant 1076, antioxidant 264, and antioxidant 626.

[0022] By adopting the above technical solution, the antioxidant is optimized and the selection of the antioxidant is facilitated.

[0023] Optionally, the antioxidants are two kinds of antioxidants, namely antioxidant 1010 and antioxidant 1076, and the weight ratio of antioxidant 1010 to antioxidant 1076 is (1-3):(1-3). In multiple embodiments, the weight ratio of antioxidant 1010 to antioxidant 1076 is 1:1, and the weight ratio can also be set to 1:2, 1:3, 2:1, 2:3, 3:1, 3:2 as needed, but it is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0024] In a second aspect, the present application provides a method for preparing the biodegradable nonwoven fabric, which adopts the following technical solution: A method for preparing the biodegradable nonwoven fabric comprises the following steps: T1, mixing polypropylene, biodegradable masterbatch, modified chitosan, maleic anhydride grafted polypropylene, and antioxidant to obtain a mixture; T2. Heat and melt the mixed material, extrude, spin, draw, and lay a web to obtain a non-woven fabric.

[0025] By adopting the above technical solution, the preparation of non-woven fabrics is facilitated.

[0026] Optionally, in step T2, the melting temperature is 250-270° C. In multiple embodiments, the melting temperature is 265° C., and the melting temperature can also be set to 250° C., 255° C., 260° C., 270° C. as required, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0027] Optionally, in step T2, the spinning temperature is 240-260° C. In many embodiments, the melting temperature is 250° C., and the spinning temperature can also be set to 240° C., 245° C., 255° C., 260° C. as required, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0028] Optionally, in step T2, the drawing temperature is 250-270° C. In multiple embodiments, the melting temperature is 260° C., and the drawing temperature can also be set to 250° C., 255° C., 265° C., 270° C. as required, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0029] Optional, non-woven fabric weight is 20-30g / m 2 In various embodiments, the nonwoven fabric has a grammage of 25 g / m 2The non-woven fabric weight can also be set to 20g / m 2 , 23g / m 2 , 28g / m 2 , 30g / m 2 , but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] In summary, this application has at least the following beneficial effects: 1. The biodegradable non-woven fabric of the present application has the advantages of high breaking strength and good degradability through the mutual cooperation between the raw materials. The longitudinal breaking strength of the non-woven fabric is greater than 74N, the transverse breaking strength is greater than 60N, and the 180-day degradation rate is greater than 90%. The scope of application is expanded, and the environmental pollution problem caused by the difficulty in degradation of traditional polypropylene non-woven fabrics can be solved.

[0031] 2. In the preparation method of modified chitosan of the present application, chitosan is first alkalized with sodium hydroxide, and then 1-chlorododecane and 4-(2-chloroethane acylamino) ethyl benzoate are grafted using chlorine groups, and active groups such as dodecyl groups, ester groups, and amide groups are introduced on the surface of chitosan to increase the compatibility of the modified chitosan and the bonding force with the raw materials. On the basis of not affecting the degradation rate of the non-woven fabric, the breaking strength of the non-woven fabric is significantly increased, so that the non-woven fabric exhibits better mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a visual observation picture of the non-woven fabric in Example 1 of the present application before degradation.

[0033] Figure 2 This is a visual observation picture of the degradation of the non-woven fabric in Example 1 of the present application for 180 days. DETAILED DESCRIPTION

[0034] In order to make the present application easier to understand, the present application will be further described in detail below in conjunction with the examples, which are merely illustrative and are not intended to limit the scope of application of the present application. The raw materials or components used in the present application can be obtained through commercial routes or conventional methods unless otherwise specified.

[0035] Preparation Example Preparation Example 1 A modified chitosan is prepared by the following method: S1. Add 80 kg of isopropyl ketone to 20 kg of water at 50°C and stir for 3 minutes. Then add 10 kg of chitosan, 10 kg of sodium hydroxide and 2 kg of tetramethylammonium hydroxide and stir for 2 hours to obtain chitosan alkaline solution.

[0036] The deacetylation degree of chitosan is 90% and the average molecular weight is 50,000.

[0037] S2. At a temperature of 70°C, add 5kg of 1-chlorododecane and 5kg of ethyl 4-(2-chloroethane acylamino)benzoate to the chitosan alkaline solution obtained in step S1, keep warm for 8 hours, and cool to 23°C. Use 8% hydrochloric acid aqueous solution to adjust the pH value to 7. Then add 100kg of acetone for precipitation. Then filter and wash three times with acetone, with 50kg of acetone used each time. Then dry to obtain modified chitosan.

[0038] Preparation Example 2 A modified chitosan is prepared by the following method: S1. Add 90 kg of isopropyl ketone to 15 kg of water at 50°C and stir for 3 minutes. Then add 10 kg of chitosan, 9 kg of sodium hydroxide and 3 kg of tetramethylammonium hydroxide and stir for 1 hour to obtain chitosan alkaline solution.

[0039] The deacetylation degree of chitosan is 90% and the average molecular weight is 50,000.

[0040] S2. At a temperature of 70°C, add 4kg of 1-chlorododecane and 6kg of ethyl 4-(2-chloroethane acylamino)benzoate to the chitosan alkaline solution obtained in step S1, keep warm for 9 hours, and cool to 23°C. Use a 10% hydrochloric acid aqueous solution to adjust the pH value to 6.5. Then add 120kg of acetone for precipitation. Then filter and wash three times with acetone, with 50kg of acetone used each time. Then dry to obtain modified chitosan.

[0041] Preparation Example 3 A modified chitosan is prepared by the following method: S1. Add 70 kg of isopropyl ketone to 25 kg of water at 50°C and stir for 3 minutes. Then add 10 kg of chitosan, 11 kg of sodium hydroxide and 1 kg of tetramethylammonium hydroxide and stir for 3 hours to obtain chitosan alkaline solution.

[0042] The deacetylation degree of chitosan is 90% and the average molecular weight is 50,000.

[0043] S2. At a temperature of 70°C, add 6kg of 1-chlorododecane and 4kg of ethyl 4-(2-chloroethane acylamino)benzoate to the chitosan alkaline solution obtained in step S1, keep warm for 7 hours, and cool to 23°C. Use a 5% hydrochloric acid aqueous solution to adjust the pH value to 7.5. Then add 80kg of acetone for precipitation. Then filter and wash three times with acetone, with 50kg of acetone used each time. Then dry to obtain modified chitosan. Example

[0044] Table 1 Amount of each raw material used in nonwoven fabrics (unit: kg) Example Example 1 Example 2 Example 3 Polypropylene 100 100 100 Biodegradable Masterbatch 1.5 1 2 Modified chitosan 7 8 6 Maleic Anhydride Grafted Polypropylene 4 5 3 Antioxidants 1.5 1 2 Example 1 A biodegradable nonwoven fabric, the raw materials and raw material ratios of which are shown in Table 1.

[0045] Among them, the melting index of polypropylene at 230°C and 2.16kg is 35g / 10min; the biodegradable masterbatch is biodegradable masterbatch JT-201, and is selected from Guangdong Limei New Material Technology Co., Ltd.; the melting index of maleic anhydride grafted polypropylene at 230°C and 2.16kg is 120g / 10min; the antioxidants are antioxidant 1010 and antioxidant 1076, and the weight ratio of antioxidant 1010 to antioxidant 1076 is 1:1; the modified chitosan is prepared by the method of Preparation Example 1.

[0046] A method for preparing a biodegradable nonwoven fabric comprises the following steps: T1. Add biodegradable masterbatch, modified chitosan, maleic anhydride grafted polypropylene and antioxidant into polypropylene, stir for 3 minutes, and obtain a mixture.

[0047] T2. The mixed material is fed into a screw extruder, heated and melted at a temperature of 265°C, extruded, spun at a temperature of 250°C, stretched at a temperature of 260°C, and laid to obtain a non-woven fabric.

[0048] The speed of the screw extruder is 80r / min; the weight of the non-woven fabric is 25g / m 2 .

[0049] Example 2 A biodegradable non-woven fabric, which is different from Example 1 in that the raw material ratio of the non-woven fabric is different, and the raw material ratio is shown in Table 1.

[0050] Example 3 A biodegradable non-woven fabric, which is different from Example 1 in that the raw material ratio of the non-woven fabric is different, and the raw material ratio is shown in Table 1.

[0051] Example 4 A biodegradable non-woven fabric is different from Example 1 in that the modified chitosan in the raw materials of the non-woven fabric has a different source, and the modified chitosan is prepared by the method of Preparation Example 2.

[0052] Example 5 A biodegradable non-woven fabric, which is different from Example 1 in that the modified chitosan in the raw materials of the non-woven fabric has a different source, and the modified chitosan is prepared by the method of Preparation Example 3.

[0053] Comparative Example Comparative Example 1 A biodegradable non-woven fabric, which is different from Example 1 in that an equal amount of polypropylene is used to replace the biodegradable masterbatch and modified chitosan in the raw materials of the non-woven fabric.

[0054] Comparative Example 2 A biodegradable non-woven fabric, which is different from Example 1 in that an equal amount of biodegradable masterbatch is used to replace modified chitosan in the raw materials of the non-woven fabric.

[0055] Comparative Example 3 A biodegradable non-woven fabric, which is different from Example 1 in that an equal amount of modified chitosan is used to replace the biodegradable masterbatch in the raw materials of the non-woven fabric.

[0056] Comparative Example 4 A biodegradable non-woven fabric, which is different from Example 1 in that an equal amount of chitosan is used to replace modified chitosan in the raw material of the non-woven fabric.

[0057] Comparative Example 5 A biodegradable non-woven fabric, which is different from Example 1 in that in the raw materials of the non-woven fabric, in the preparation method of the modified chitosan, an equal amount of 1-chlorododecane is used to replace 4-(2-chloroethane acylamino) ethyl benzoate.

[0058] Comparative Example 6 A biodegradable nonwoven fabric, which is different from Example 1 in that in the raw materials of the nonwoven fabric, in the preparation method of the modified chitosan, an equal amount of ethyl 4-(2-chloroethaneylamino)benzoate is used to replace 1-chlorododecane.

[0059] Performance Testing (1) The nonwoven fabrics obtained in Examples 1-5 and Comparative Examples 1-6 were respectively taken as samples, and the breaking strength of the samples was tested according to GB / T 24218.3-2010 "Test methods for textile nonwovens - Part 3: Determination of breaking strength and elongation at break (strip method)". The test results are shown in Table 2.

[0060] (2) The nonwoven fabrics obtained in Examples 1-5 and Comparative Examples 1-6 were respectively taken as samples, and the samples were composted and buried for 180 days according to GBT 19277.1-2011 "Determination of the ultimate aerobic biodegradability of materials under controlled composting conditions by measuring the released carbon dioxide - Part 1: General method", and the degradation rate was calculated. The test results are shown in Table 2.

[0061] At the same time, positive control group and negative control group were made. The positive control group used TLC grade cellulose, and the negative control group used polyethylene.

[0062] At the same time, the nonwoven fabric of Example 1 was visually observed before and after degradation and photographed. Figure 1 , Example 1 Nonwoven fabric degradation for 180 days Visual observation pictures are shown in Figure 2 .

[0063] Degradation rate / (%) = (net weight of silicon dioxide produced (mg) × 100%) / (sample weight (g) × ThCO2 (sample) (mgCO2 / g sample)); wherein ThCO2 is the maximum theoretical amount of carbon dioxide produced by completely oxidizing the compound.

[0064] ThCO2 / (mgCO2 / g)=TOC×(44 / 12); wherein 44 and 12 are the molecular mass of carbon dioxide and the atomic mass of carbon, respectively.

[0065] Table 2 Test results As can be seen from Table 2, the nonwoven fabric of the present application has a high breaking strength, with a longitudinal breaking strength of 74.1-76.3N and a transverse breaking strength of 60.6-62.5N, showing better mechanical properties. It also has a high degradation rate, with a 180-day degradation rate of 90.5-93.6%, showing better degradability. The nonwoven fabric of the present application has the advantages of high breaking strength and good degradability through the mutual cooperation between the raw materials, meeting market demand.

[0066] Combination Figure 1 , Figure 2 ,from Figure 1 It can be seen that the structure of the nonwoven fabric is intact before degradation. Figure 2 It can be seen that there is less residue after 180 days of degradation of the non-woven fabric, and the 180-day degradation rate of the non-woven fabric reaches 93.6%.

[0067] Comparing Example 1 with Comparative Examples 1-3, the non-woven fabric of Comparative Example 1 did not contain biodegradable masterbatch or modified chitosan; the non-woven fabric of Comparative Example 2 contained biodegradable masterbatch; the non-woven fabric of Comparative Example 3 contained modified chitosan; and the non-woven fabric of Example 1 contained biodegradable masterbatch and modified chitosan. It can be seen that the addition of biodegradable masterbatch and modified chitosan to the raw materials of the non-woven fabric has little effect on the breaking strength of the non-woven fabric, but the synergistic effect between them can significantly improve the degradation rate and make the non-woven fabric show better degradability.

[0068] Comparing Example 1 with Comparative Examples 4-6, chitosan was added to the nonwoven fabric of Comparative Example 4; chitosan modified by sodium hydroxide and 1-chlorododecane was added to the nonwoven fabric of Comparative Example 5; chitosan modified by sodium hydroxide and ethyl 4-(2-chloroethane acylamino)benzoate was added to the nonwoven fabric of Comparative Example 6; chitosan modified by sodium hydroxide, 1-chlorododecane, and ethyl 4-(2-chloroethane acylamino)benzoate was added to the nonwoven fabric of Example 1. It can be seen that the modification of chitosan does not substantially affect the degradation rate of the nonwoven fabric, but the grafting of chitosan with 1-chlorododecane and ethyl 4-(2-chloroethane acylamino)benzoate at the same time and the mutual cooperation between the two can improve the compatibility of chitosan and the raw materials, and improve the breaking strength of the nonwoven fabric, so that the nonwoven fabric exhibits better mechanical properties.

[0069] It should be noted that the embodiments described above are only used to explain the present application and do not constitute any limitation to the present application. The present application is described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present application may be modified as specified within the scope of the claims of the present application, and the present invention may be revised without departing from the scope and spirit of the present application. Although the present application described therein relates to specific methods, materials and embodiments, it does not mean that the present application is limited to the specific examples disclosed therein. On the contrary, the present application can be extended to all other methods and applications with the same functions.

Claims

1. A biodegradable nonwoven fabric, characterized in that: The invention is mainly made of the following raw materials in parts by weight: 100 parts of polypropylene, 1-2 parts of biodegradable masterbatch, 6-8 parts of modified chitosan, 3-5 parts of maleic anhydride grafted polypropylene and 1-2 parts of antioxidant; the modified chitosan is obtained by treating chitosan with sodium hydroxide, 1-chlorododecane and 4-(2-chloroethane acylamino) ethyl benzoate.

2. The biodegradable nonwoven fabric according to claim 1, characterized in that: The modified chitosan is prepared by the following method: S1. Mix water, isopropyl ketone, chitosan, sodium hydroxide and tetramethylammonium hydroxide at a temperature of 40-60°C, and stir for 1-3 hours to obtain chitosan alkaline solution; S2. Add 1-chlorododecane and ethyl 4-(2-chloroethaneylamino)benzoate to the chitosan alkaline solution at a temperature of 60-80°C, keep the temperature for 7-9 hours, cool to room temperature, adjust the pH value to 6.5-7.5, add acetone for precipitation, filter, wash, and dry to obtain modified chitosan.

3. The biodegradable nonwoven fabric according to claim 2, characterized in that: The weight ratio of chitosan, sodium hydroxide, 1-chlorododecane and ethyl 4-(2-chloroethane acylamino)benzoate is 10:(9-11):(4-6):(4-6).

4. The biodegradable nonwoven fabric according to claim 2, characterized in that: The weight ratio of the chitosan, water, isopropyl ketone, tetramethylammonium hydroxide and acetone is 10:(15-25):(70-90):(1-3):(80-120).

5. The biodegradable nonwoven fabric according to claim 2, characterized in that: The deacetylation degree of the chitosan is 85-95%.

6. The biodegradable nonwoven fabric according to claim 2, characterized in that: In step S2, the pH value is adjusted to 6.5-7.5 using a hydrochloric acid aqueous solution, and the mass concentration of the hydrochloric acid aqueous solution is 5-10%.

7. The biodegradable nonwoven fabric according to claim 1, characterized in that: The polypropylene has a melt index of 30-40 g / 10 min at 230° C. and 2.16 kg.

8. The biodegradable nonwoven fabric according to claim 1, characterized in that: The maleic anhydride grafted polypropylene has a melt index of 100-150 g / 10 min at 230° C. and 2.16 kg.

9. The biodegradable nonwoven fabric according to claim 1, characterized in that: The antioxidant is one or more of antioxidant 1010, antioxidant 1076, antioxidant 264, and antioxidant 626.

10. A method for preparing a biodegradable nonwoven fabric according to any one of claims 1 to 9, characterized in that: The steps include: T1, mixing polypropylene, biodegradable masterbatch, modified chitosan, maleic anhydride grafted polypropylene, and antioxidant to obtain a mixture; T2. Heat and melt the mixed material, extrude, spin, draw, and lay a web to obtain a non-woven fabric.

Citation Information

Patent Citations

  • Biodegradable polyester fibre and preparation method thereof

    CN111235688A

  • Polylactic acid grafted quaternized chitosan material, stereocomplex crystal nanofiber membrane of polylactic acid grafted quaternized chitosan material, and preparation methods and applications of polylactic acid grafted quaternized chitosan material and stereocomplex crystal nanofiber membrane

    CN111662457A

  • Durable antibacterial polypropylene non-woven fabric and preparation method thereof

    CN112695526A

  • Manufacturing method of natural-color degradable and dispersible non-woven fabric

    CN112981721A

  • Modified chitosan high-temperature-resistant salt-resistant filtrate reducer as well as preparation method and application thereof

    CN113929817A